HUBUNGAN ANTARA KEPUASAN KONSUMEN DENGAN INTENSITAS PENGGUNAAN KARTU PRABAYAR - Mayreyna Nurwardani; Sumaryono Sumaryono (JURNAL SPIRITS, 2013)
ABSTRACTThis research aimed to find out the relationship between customer satisfaction and the intensity of using prepaid cards such as Simpati,Mentari,Pro XL and Im3.The subject of this research are 40 students of Faculty Y State Universities in Yogyakarta, the range of the age between 18-26 years old, assuming they have gadget. Data collected by using consumer satisfaction scale, the intensity using demographic, and interviews. Unfortunately the result show there is no relationship between customer satisfaction and the intensity of use of prepaid cards.Key words:consumer satisfaction, the intensity of the use of prepaid cards